Chemical Bonding and Local Islamic Wisdom of Sasak Tribe, Lombok, West Nusa Tenggara - Adi Fadli (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2018)
A myriad of traditions underlie the local wisdom of Sasak tribe (the indigenous people in Lombok), namely tradisi merarik (wedding), nenarih (proposing), sorong serah ajikrame (dowry negotiation), langar, begawe (party) , banjar (the community body), begibung (eating together), berayan mangan (eating together), and nyongkolan (wedding parade). Such local customs in general entail the value of mutual concession or tolerance, compassion, dependency, social solidarity, sympathy, communal work for peace, and prosperity. The local wisdoms are strongly relevant to the theory of chemical bonding such as electrostatic stability and configuration, the positive and negative ions, theory of chemical bond formation, polar and nonpolar covalent, coordinate covalent bond, metal bonding, and intermolecular forces comprising hydrogen and Van der Waals bond. The interface and relevance of both are actualized in the religious and social values of Sasak Lombok tradition equivalent to the theory of chemical bonding. Therefore, this paper demonstrates that the theory of chemical bonding is strongly relevantly associated with the tradition of local Islamic wisdom of Sasak Lombok, West Nusa Tenggara.